(untitled) (Cadernos de Sociomuseologia, 2026)
The Museum of Footwear and Industry in Inca (Mallorca) was created in the early twenty-first century as an initiative to preserve the industrial memory of a town deeply linked to shoe production. However, after its opening in 2010, the museum’s social perception among the local population was marked by indifference, disaffection and, in some cases, rejection. Rather than being understood as a space of shared identity, it was perceived as a mausoleum of a recent past in crisis. In this context, the article analyses, through a longitudinal study carried out between 2017 and 2023, how the application of Sociomuseology and the implementation of visitor studies contributed to transforming that initial perception. Methodologically, the research is based on a mixed approach, using focus groups, surveys, polls and participant observation with actual visitors, potential visitors and non-publics. The results show that the museum’s transformation did not depend only on new content, but also on the way it was constructed, mediated and socially validated. Community participation in the redefinition of narratives, mediation resources and educational activities fostered a symbolic reappropriation of the museum as a common territory, a space of listening, living memory and intergenerational dialogue. In sum, the case shows that the social perception of the museum is dynamic and that, when genuine participatory processes are activated, the institution can recover legitimacy and strengthen its territorial relevance. Keywords: sociomuseology; social perception; visitor studies; community participation; industrial memory